2022
DOI: 10.3991/ijim.v16i23.36225
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mobile Technology Use in an Interactive Distance Education Classroom Environment

Abstract: The aim of this study is to investigate the determination of university students’ use of mobile technology in an interactive distance education classroom environment. The quantitative research method was used in the research. The research was conducted in the fall semester of 2021–2022. A total of 318 university students continuing their education in Kazakhstan voluntarily participated in the research. In the research, a 4-week online training was given to university students. The ‘distance education and mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The development of VLLE on metaverse is based on the integration of new technological concepts, with an effort to provide students-who must be simulated themselves in the form of a 3D avatar-with hands-on learning experiences in a virtual learning environment. The concepts and theories include virtual learning environment [6], [8][9][10], virtual reality technology [1], [11], virtual laboratory [12], [13], metaverse [7], [14], [15], and mobile technology [20], [21]. The conceptual framework of this research is shown in Figure 1.…”
Section: Phase 1: Synthesis Of Conceptual Framework For the Developme...mentioning
confidence: 99%
“…The development of VLLE on metaverse is based on the integration of new technological concepts, with an effort to provide students-who must be simulated themselves in the form of a 3D avatar-with hands-on learning experiences in a virtual learning environment. The concepts and theories include virtual learning environment [6], [8][9][10], virtual reality technology [1], [11], virtual laboratory [12], [13], metaverse [7], [14], [15], and mobile technology [20], [21]. The conceptual framework of this research is shown in Figure 1.…”
Section: Phase 1: Synthesis Of Conceptual Framework For the Developme...mentioning
confidence: 99%